PENGARUH MODEL PEMBELAJARAN TGT BERBANTUAN MEDIA ROMA TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Mariyanti, Mariyanti; Anitra, Rien; Rosdianto, Haris (JRPD (Jurnal Riset Pendidikan Dasar), 2025)
This research aims to: 1) determine the effect of the TGT learning model assisted by ROMA Media on the mathematics learning outcomes of class IV students at SDN 11 Bentunai; 2) find out how much influence the application of the TGT learning model assisted by ROMA Media has on the mathematics learning outcomes of class IV students at SDN 11 Bentunai. The research method used was Quasi Experimental with a Nonequivalent Posttest-Only Control Group Design. The population in this study were fourth grade students at SDN 11 Bentunai. The research sample was taken using non-probability sampling with a saturated sample. The prerequisite tests carried out were a normality test using SPSS version 25 and a homogeneity test to see the similarity of the variants of the two groups. Data analysis was carried out universally with a significance level of 0.05. Testing the first hypothesis used the independent sample t-test, testing the second hypothesis using the effect size test, and testing the third hypothesis using the average formula. The results of the research show that: 1) the influence of the TGT learning model assisted by ROMA Media on students' mathematics learning outcomes. This is proven by the independent sample t-test of 0.007, which is smaller () than 0.05; 2) moderate influence of the application of the TGT learning model assisted by ROMA Media on students' mathematics learning outcomes. This is proven by the effect size test of 0.75 in the medium category.